USING JUST A MINUTE GAME TO IMPROVE STUDENTS’ SPEAKING ABILITY IN SENIOR HIGH SCHOOL - Rinindi Pertiwi; Zul Amri (Universitas Negeri Padang, 2017)
This article discusses about an interactive game that can encourage students to speak communicatively. The game named Just a Minute Game. Just a Minute game is a simple game but effective to improve students’ speaking skill. The rule of the game is the students speak in one minute about a topic given by teacher without hesitation, repetition, and deviation. If the students break the rule, the other students can take the chance by saying “Challenge”. The teacher can choose the students who will continue the speech with the same topic. The student who can speak in one minute without breaking the rule will be the winner of the game. Through this game, the students are expected to be interested in learning English, especially in speaking.